Determination of Partition Coefficients of Selected Model Migrants between Polyethylene and Polypropylene and Nanocomposite Polypropylene - Pablo Otero-Pazos; David A. Pereira de Abreu; Raquel Sendon; Ana Rodriguez Bernaldo de Quiros; Inmaculada Angulo; Jose M. Cruz; Perfecto Paseiro-Losada (Journal of Chemistry)
Studies on nanoparticles have focused the attention of the researchers because they can produce nanocomposites that exhibit unexpected hybrid properties. Polymeric materials are commonly used in food packaging, but from the standpoint of food safety, one of the main concerns on the use of these materials is the potential migration of low molecular substances from the packaging into the food. The key parameters of this phenomenon are the diffusion and partition coefficients. Studies on migration from food packaging with nanomaterials are very scarce. This study is focused on the determination of partition coefficients of different model migrants between the low-density polyethylene (LDPE) and polypropylene (PP) and between LDPE and nanocomposite polypropylene (naPP). The results show that the incorporation of nanoparticles in polypropylene increases the mass transport of model migrants from LDPE to naPP. This quantity of migrants absorbed into PP and naPP depends partially on the nature of the polymer and slightly on the chemical features of the migrant. Relation (RPP/naPP) between partition coefficient KLDPE/PP and partition coefficient KLDPE/naPP at 60°C and 80°C shows that only BHT at 60°C has a RPP/naPP less than 1. On the other hand, bisphenol A has the highest RPP/naPP with approximately 50 times more.